Marked Decrease in Rotavirus Detections Among Preschool Children Unvaccinated for Rotavirus in the Netherlands, 2014. Issue 7 (July 2016) - Pijnacker, Roan; Mughini-Gras, Lapo; Vennema, Harry; Duizer, Erwin; Pelt, Wilfrid van
Abstract : Rotavirus detection rates among preschool children sampled irrespective of symptoms during the rotavirus season (January–April) in the Netherlands were significantly lower in 2014 (0.6%) than in 2010 (11.2%), 2011 (6.9%), 2012 (6.8%) and 2013 (6.7%). This supports previous observations of a genuine drop in rotavirus circulation (without rotavirus vaccination) rather than a milder disease course.